Amphipathic Phenylalanine-Induced Nucleophilic–Hydrophobic Interface Toward Highly Reversible Zn Anode - Anbin Zhou; Huirong Wang; Fengling Zhang; Xin Hu; Zhihang Song; Yi Chen; Yongxin Huang; Yanhua Cui; Yixiu Cui; Li Li; Feng Wu; Renjie Chen (Nano-Micro Letters, 2024)
Highlights The amphipathic phenylalanine-adsorbed layer contributes to form a nucleophilic–hydrophobic interface that homogenizes Zn2+ flux while repelling H2O molecules from contacting Zn anode. The preferential reduction of phenylalanine (Phe) prior to H2O facilitates in situ formation of an organic–inorganic hybrid solid electrolyte interphase, enhancing the interfacial stability. Benefiting from the triple protection of Phe, the Zn||Zn and Zn||LMO cells display significantly improved electrochemical performances, even at extreme diluted electrolytes.